2021
DOI: 10.1590/s0102-8529.2019430100007
|View full text |Cite
|
Sign up to set email alerts
|

From Panda to Dragon: An Analysis of China’s Maritime Actions and Reactions in the East China Sea and Their Implications since 2012

Abstract: In the 21st century, China’s rise has been shifting global and regional geopolitical scenarios. Faced with its growth and fears of being perceived as a threat, China sought to associate its economic and political emergence with the preservation of the current international system, emphasizing speeches about a peaceful development and harmonious world in which it would be an actor who wants to grow and accommodate the world order. However, changes in the balance of power and its continued rise have caused China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Those can be important means, capable of assisting the government to stay in power and change security and foreign policies (Morgenthau 1948;Carr 2001;Kitchen 2010;Schweller 2018;Oliveira 2019;2021). That's why propaganda about threats can strengthen the national cohesion or the very character of the Nation (Sterling-Folker 2009; Morgenthau 1948), or even stimulate in-group and out-group perceptions.…”
Section: Domestic Mobilization and Propagandamentioning
confidence: 99%
See 4 more Smart Citations
“…Those can be important means, capable of assisting the government to stay in power and change security and foreign policies (Morgenthau 1948;Carr 2001;Kitchen 2010;Schweller 2018;Oliveira 2019;2021). That's why propaganda about threats can strengthen the national cohesion or the very character of the Nation (Sterling-Folker 2009; Morgenthau 1948), or even stimulate in-group and out-group perceptions.…”
Section: Domestic Mobilization and Propagandamentioning
confidence: 99%
“…Japan argues that those islands were incorporated into its territory through Okinawa Prefecture in 1895, after the authorities concluded that there had been no previous occupation of these territories by another country. In the Post-World War II period, Japan considers that the islands came under US control due to the San Francisco Treaty (1951) and returned to Japan in 1972 with the Reversion of Okinawa (Oliveira 2019;2021).…”
Section: Domestic Mobilization and Propagandamentioning
confidence: 99%
See 3 more Smart Citations